Study on preparation of CNTs-Cu composites materials by chemical coprecipitation hydrogen reduction solid state sintering process. Issue 183 (2nd September 2017) - Yulong, Li; Yifei, Luo; Bohui, Li; Zaiyuan, Li
ABSTRACT: The CNTs-CuO composite powders were synthesized by chemical co-precipitation method, when the co-precipitation temperature was set as 70°C, stirring rate was set to 1000 rpm, pH was 10, drip reaction time was 120 min and the drying temperature was 50°C. Carbon nanotubes (CNTs), Copper sulfate, sodium hydroxide were used as raw materials. 8%CNTs-Cu and 16%CNTs-Cu composite powders were synthesized by hydrogen reduction, reduced at 300°C for 2h. 8%CNTs-Cu composite bulk were prepared by a solid-phase sintering process when the molding temperature was 800°C, while 16%CNTs-Cu composite bulk cannot be prepared by the same method.